2018
DOI: 10.1002/chem.201800923
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Avibactam Derivatives and Activity on β‐Lactamases and Peptidoglycan Biosynthesis Enzymes of Mycobacteria

Abstract: There is a renewed interest for β-lactams for treating infections due to Mycobacterium tuberculosis and M. abscessus because their β-lactamases are inhibited by classical (clavulanate) or new generation (avibactam) inhibitors, respectively. Here, access to an azido derivative of the diazabicyclooctane (DBO) scaffold of avibactam for functionalization by the Huisgen-Sharpless cycloaddition reaction is reported. The amoxicillin-DBO combinations were active, indicating that the triazole ring is compatible with dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Variations were observed between the different diazabicyclooctane (DBO)‐type inhibitors tested; moderate inhibition was observed for zidebactam and avibactam, whereas relebactam did not inhibit Ldt Mt2 at the levels tested. The targeting of Ldts by DBO inhibitors has been observed in previous work showing that avibactam potentiates the activity of the penicillin amoxicillin against M. tuberculosis . Interestingly, the cyclic boronate β‐lactamase inhibitor vaborbactam did not inhibit Ldt Mt2 under these conditions, potentially due to the different interactions of active‐site serine and cysteine residues with boron.…”
Section: Resultsmentioning
confidence: 51%
“…Variations were observed between the different diazabicyclooctane (DBO)‐type inhibitors tested; moderate inhibition was observed for zidebactam and avibactam, whereas relebactam did not inhibit Ldt Mt2 at the levels tested. The targeting of Ldts by DBO inhibitors has been observed in previous work showing that avibactam potentiates the activity of the penicillin amoxicillin against M. tuberculosis . Interestingly, the cyclic boronate β‐lactamase inhibitor vaborbactam did not inhibit Ldt Mt2 under these conditions, potentially due to the different interactions of active‐site serine and cysteine residues with boron.…”
Section: Resultsmentioning
confidence: 51%
“…Observations that avibactam reduces the MIC of several β-lactams against Mab provides further validation of its efficacy against both the Bla Mab protein and whole-cell Mab (Dubee et al, 2015a ; Kaushik et al, 2017 ; Lefebvre et al, 2017 ). A recent study showed avibactam not only inhibits β-lactamases but also inhibits LDTs (Edoo et al, 2018 ). A recombinant Mab strain lacking bla Mab exhibited increased sensitivity to β-lactams and was rendered susceptible to amoxicillin and ceftaroline (Lefebvre et al, 2016 ).…”
Section: Factors That Determine Potency Of β-Lactams Against mentioning
confidence: 99%
“…However, Bla Mab is inactivated by the non-␤-lactam ␤-lactamase inhibitor avibactam, resulting in the reduction of the MICs of several ␤-lactams against M. abscessus upon the addition of avibactam (25,38,40,41). Avibactam may also directly inhibit LDTs (42), which may potentiate the synergy observed between dual ␤-lactams. In addition, relebactam and vaborbactam, which are also non-␤-lactam ␤-lactamase inhibitors, reduce MICs of various ␤-lactams against M. abscessus when combined (43).…”
mentioning
confidence: 99%